OsPRD2 is essential for double-strand break formation, but not spindle assembly during rice meiosis - Wang, Chong; Qu, Shuying; Zhang, Jie; Fu, Ming; Chen, Xiaofei; Liang, Wanqi (Frontiers in Plant Science, 2023)
Meiotic recombination starts with the programmed formation of double-strand breaks (DSB) in DNA, which are catalyzed by SPO11, a type II topoisomerase that is evolutionarily conserved, and several other accessary proteins. Homologs of MEIOSIS INHIBITOR 4 (MEI4/REC24/PRD2) are proteins that are also essential for the generation of meiotic DSBs in budding yeast, mice and Arabidopsis thaliana. In Arabidopsis, the protein ARABIDOPSIS THALIANA PUTATIVE RECOMBINATION INITIATION DEFECTS 2/MULTIPOLAR SPINDLE 1 (AtPRD2/MPS1) has been shown to have additional roles in spindle assembly, indicating a functional diversification. Here we characterize the role of the rice MEI4/PRD2 homolog in meiosis. The osprd2 mutant was completely male and female sterile. In male meiocytes of osprd2, no rH2AX foci were detected and twenty-four univalents were produced at diakinesis, suggesting that OsPRD2 is essential for DSB generation. OsPRD2 showed a dynamic localization during meiosis. For instance, OsPRD2 foci first appeared as discrete signals across chromosome at leptotene, and then became confined to the centromeres during zygotene, suggesting that they might be involved in assembly of the spindle. However we did not observe any obvious aberrant morphologies in neither the organization of the bipolar spindle nor in the orientation of the kinetochore in the mutant. These findings suggest that in rice PRD2 might not be required for spindle assembly and organization, as it does in Arabidopsis. Taken together our results indicate that plant MEI4/PRD2 homologs do play a conserved role in the formation of meiotic DSBs in DNA, but that their involvement in bipolar spindle assembly is rather species-specific.